The role of hematopoietic stem cell transplantation in the treatment of relapsed/refractory Hodgkin's lymphoma - Sureda, Anna; Pereira, Maria I. Barbosa; Dreger, Peter (Current opinion in oncology, 2012)
Purpose of review: Autologous stem cell transplantation (ASCT) represents the treatment of choice for primary refractory or relapsed Hodgkin's lymphoma patients. Nevertheless, the results of ASCT are not universally uniform in all groups of patients. Allogeneic stem cell transplantation (allo-SCT) has increasingly been used to rescue failures after an ASCT. Its use is going to be potentially challenged by the advent of targeted therapy. Recent findings: Comprehensive information regarding prognostic factors in the ASCT setting that can allow to discriminate specific groups potentially candidates for other therapies is presented as well as an updated summary of the potential role of reduced intensity allo-SCT in relapsed patients including the largest phase II prospective clinical trial. Outcome of multiply relapsed Hodgkin's lymphoma patients treated with single-dose brentuximab vedotin, a new anti-CD30 monoclonal antibody, is discussed. Summary: ASCT results might well be implemented by improving the quality of the remission of patients undergoing the procedure with more effective salvage protocols or by selecting those patients who might better benefit from the procedure. Results of allo-SCT as well as the percentage of patients potentially candidates for the procedure will also be able to be modified with a better selection of the patients and the use of targeted and less toxic therapy to render patients into an adequate response.